Harmonizing scientific rigor with political urgency: policy learnings for identifying accelerators for scale-up from the safe childbirth checklist programme in Rajasthan, India - Somesh Kumar; Priti Dave; Ashish Srivastava; Jelle Stekelenburg; Dinesh Baswal; Deepti Singh; Bulbul Sood; Vikas Yadav (BMC, 2019)
Abstract Background Quick scaling-up of innovative and promising interventions in health systems of low and middle-income countries to rapidly achieve population level benefits is a key challenge. While there is consensus on the need for rigorous scientific evidence on effectiveness of interventions before considering scale-up, there can be significant time lag for the want of gold-standard evidence. The Safe Childbirth Checklist (SCC) programme in India, demonstrated how an innovation was robustly evaluated and scaled up nationally, within a short span of time. In this narrative review, we describe the strategies discussed in various published scale-up frameworks and map them against the strategies adopted by the SCC programme to identify accelerators which facilitated its rapid scale up. Methods The narrative review - done from May to June 2017 - involved keyword searches of electronic databases of PubMed, Ovid Medline and Google Scholar. It included the key words 'pilot', 'health innovations', 'scale-up', 'replication', 'expansion', 'increased coverage', 'conceptual models for scale-up', 'frame-works for scale-up', 'evidence for scale-up' in the title of publications,. This search was limited to publications in English after the year 1995. We used snowball sampling approach (by referring to bibliographies of shortlisted publications) to identify additional publications related to scale-up. We then screened the identified publications independently and relevant publications that discussed attributes for a conceptual model for scale-up of public health interventions in low and middle-income countries were shortlisted. We then mapped the strategies we used in SCC program scale up against those described in the shortlisted frameworks to identify seven accelerators which facilitated rapid scale up. Results The identified accelerators were: testing the intervention in real world, resource constrained settings; using an appropriate and time sensitive research design; testing the intervention at substantial scale and in diverse settings; using an adaptive and iterative prototyping approach for implementation; sharing data and evidence with key stakeholders on an ongoing basis; targeting bridge resources through strategic engagement of stakeholders and timely integration of scale-up plans with annual planning and budgeting cycles and systems. Conclusion These accelerators will complement current frameworks and provide guidance to future scale-up initiatives in India and elsewhere.